Condições equivalentes de projeto baseadas no fator de utilização de longo prazo na TDZ para risers de aço em catenária - Marroquin, Oscar Alfredo Godoy (2017)
This work presents a semi-analytical methodology to select design environmental conditions based on long-term cross-section utilization ratios at the TDZ (Touchdown Zone) for steel catenary risers. This approach uses simplified analytical models to calculate time series of short-term utilization ratios, defined according to the DNV-OS-F201 (2010) standard. The low computational cost allows the effective determination of long-term utilization ratios. By evaluating long-term utilization ratios, it is possible to define short-term design environmental conditions, defined as short-term conditions whose most probable extreme responses are equal to the long-term ones. This kind of methodology may represent a substantial change to the traditional focus given to riser design, which is based on responses obtained from extreme environmental conditions, instead of on the extreme responses.